QTL mapping of root hair and acid exudation traits and their relationship to phosphorus uptake in common bean - Yan, X; Liao, H; Beebe, Stephen E.; Blair, Matthew W.; Lynch, Jonathan P. (Springer, 2004)
The relationship between root-hair growth, acid exudation and phosphorus (P) uptake as well as the quantitative trait loci (QTLs) associated with these traits were determined for a recombinant inbred line (RIL) population derived from the cross of two contrasting common bean (Phaseolus vulgaris L.) genotypes, DOR364 and G19833, which were grown in solution culture and under field conditions with low-P availability. In the solution-culture study, root-hair density, root-hair length, H+ exudation and total acid exudation were measured. Substantial genotypic variability was observed for these traits and their response to P availability. The P-efficient parent G19833 had greater root-hair density, longer root-hair length, and greater exudation of H+ and total acid than the P-inefficient genotype DOR364. These traits segregated continuously in the RIL population, with obvious tendency of trait transgression. Genetic analysis revealed that the root traits measured had various heritabilities, with h b 2 ranging from 43.24 to 86.70%. Using an integrated genetic map developed for the population, a total of 19 QTLs associated with root hair, acid exudation and P-uptake traits were detected on 8 linkage groups. P uptake in the field was positively correlated with total acid exudation, basal root-hair length, and basal root-hair density. Acid-exudation traits were intercorrelated, as were root-hair traits. Total acid exudation was positively correlated with basal root-hair density and length. Linkage analysis revealed that some of the root-trait QTLs were closely linked with QTLs for P uptake in the field. We propose that marker-assisted selection (MAS) might be a feasible alternative to conventional screening of phenotypic root traits.